Critical Analysis of Mutual Fund in India - Mishra, Chandradeep; Kansal, Mani (Journal of Commerce and Trade, 2008)
The Indian capital market has been increasing tremendously during last few years. With the reforms of economy, reforms of industrial policy, reforms of public sector and reforms of financial sector, the economy has been opened up and many developments have been taking place in the Indian money market and capital market. During last one decade or so, role of Indian mutual funds industry as a significant financial service in financial market has really been noteworthy. They now play a very significant role in channelizing the saving of millions of individuals into the investment in equity and debt instrument. The main objective of this paper is to examine the importance and growth of mutual funds and evaluate the operations of mutual funds and suggest some measures to make it a successful scheme in India.